LiquidML: A Model Based Environment for Developing High Scalable Web Applications - Robles Luna, Esteban (2014)
The scalability of modern Web applications has become a key aspect for any business in order to support thousands of concurrent users while reducing its computational costs. However, existing model driven web engineering approaches have been focus on building Web applications that satisfy functional requirements while disregarding “technological” aspects such as scalability and performance. As a consequence, the applications derived from these approaches may not scale well and need to be adapted. In this paper we present the LiquidML environment, which allows building Web applications using a model-based approach. In contrast with existing approaches, aspects that help to improve the scalability of a Web application are modeled as first class citizens and as a consequence the applications obtained scale better than its counterparts.